2016
DOI: 10.1371/journal.pone.0164656
|View full text |Cite
|
Sign up to set email alerts
|

Biological Role of Paenilarvins, Iturin-Like Lipopeptide Secondary Metabolites Produced by the Honey Bee Pathogen Paenibacillus larvae

Abstract: The Gram-positive bacterium Paenibacillus larvae (P. larvae) is the causative agent of a deadly honey bee brood disease called American Foulbrood (AFB). AFB is a notifiable epizootic in most countries and, hence, P. larvae is of considerable relevance for veterinarians and apiculturists alike. Over the last decade, much progress has been made in the understanding of the (patho)biology of P. larvae. Recently, several non-ribosomally produced peptides (NRP) and peptide/polyketide (NRP/PK) hybrids produced by P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…This result is consistent with our mass spectrometry data of paenilipoheptins. Interestingly, Paenibacillus larvae , a honey bee pathogen inducing the American foulbrood, produces a family of lipoheptapeptides, the paenilarvins, which are directly related to iturins …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with our mass spectrometry data of paenilipoheptins. Interestingly, Paenibacillus larvae , a honey bee pathogen inducing the American foulbrood, produces a family of lipoheptapeptides, the paenilarvins, which are directly related to iturins …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Paenibacillus larvae,ahoney bee pathogen inducing the Americanf oulbrood, produces af amily of lipoheptapeptides, the paenilarvins,w hicha re directly related to iturins. [29,30] Cyclic lipoheptapeptides are frequently used motifs of Bacillales. Well known are the heptapeptide compounds surfactins and iturins produced by numerous B. subtilis and B. amyloliquefaciens strains [50,51] that exhibit manifold valuable activities, such as antimicrobial, antiviral, and antimycoplasmatic effects, which qualify them for both medical and biotechnological applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results led to a better understanding of the virulence differences and showed that the two genotypes follow different molecular strategies during the invasive phase of infection (Djukic et al ., ; Poppinga and Genersch, ). Differential production of several secondary metabolites was demonstrated (Garcia‐Gonzalez et al ., ; Hertlein et al ., ; Müller et al ., ; Sood et al ., ) including paenilamicin, which is produced by P. larvae ERIC II only and was shown to suppress the growth of bacterial competitors in the larval gut (Müller et al ., ; Müller et al ., ). A key virulence factor of both P. larvae ERIC I and ERIC II is Pl CBP49, a chitin‐degrading enzyme responsible for the destruction of the peritrophic matrix during infection (Garcia‐Gonzalez and Genersch, ; Garcia‐Gonzalez et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, P. larvae produces some antibacterial peptides against competing microorganisms: Paenilamicins acts against bacteria and Paenilarvin acts against fungal competitors .…”
Section: Introductionmentioning
confidence: 99%